Preparation, characterization and in vitro anticoagulant activity of corn stover xylan sulfates. Issue 3 (11th February 2017) - Cheng, He-Li; Liu, Hao; Feng, Qing-Hua; Xie, Yi-Min; Zhan, Huai-Yu
Abstract: A new anticoagulant agent was prepared by introducing sulfate groups into corn stover xylan through homogeneous reactions. Three organic solvents, N, N -dimethylformamide (DMF), dimethyl sulfoxide (DMSO) and formamide (FA), were adopted as reaction media, with the assistance of LiCl. Structural characterization by FT-IR and 13 CNMR showed that xylan sulfate (XS) could be successfully synthesized with SO3 ∙Pyridine (SO3 ∙Py) complexes sulfation reagent in the three media. The effect of sulfation temperature, sulfation time, media type and molar ratio of −SO3 /−OH on the degree of substitution (DS) and degree of the polymerization (DP) were studied. DMF/LiCl were more effective than DMSO/LiCl and FA/LiCl in preparation of xylan sulfate with high DS. The optimal conditions for sulfation were obtained when SO3 ∙Py complex was added to DMF/LiCl with −SO3 /−OH ratio of 1.5:1 and maintained at 50 °C for 3 h. Degree of polymerization of xylan was decreased during the sulfation process and DMF/LiCl offered the least xylan degradation as compared with DMSO/LiCl or FA/LiCl. Anticoagulant activities of the resultant xylan sulfates with different DS were evaluated by using activated partial thromboplastin time (APTT), thrombin time (TT), and prothrombin time (PT). Results indicated that the introducing of sulfate groups into xylan did endow the polysaccharides with anticoagulant activity. The APTT and TT of XS with DS of 1.20 reached 141 and 45.3 s at a dosage of 20 μg/mL, while the APTT and TT values for the blank sample were only 35.5 and 15.6 s. Furthermore, coagulation time was prolonged with the increase of DS and the concentration of XS. Our findings provide new insights into the value-added utilization of agricultural biomass.